2013
DOI: 10.1007/s10773-013-1620-5
|View full text |Cite
|
Sign up to set email alerts
|

Lie Symmetries for a Conformally Flat Radiating Star

Abstract: We consider a relativistic radiating spherical star in conformally flat spacetimes. In particular we study the junction condition relating the radial pressure to the heat flux at the boundary of the star which is a nonlinear partial differential equation. The Lie symmetry generators that leave the equation invariant are identified and we generate an optimal system. Each element of the optimal system is used to reduce the partial differential equation to an ordinary differential equation which is further analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…which is a self-similar solution for the master equation. It has been obtained previously by Abebe et al [23] when analyzing a conformally flat radiating star.…”
Section: Hence We Have the Potentialsmentioning
confidence: 60%
See 1 more Smart Citation
“…which is a self-similar solution for the master equation. It has been obtained previously by Abebe et al [23] when analyzing a conformally flat radiating star.…”
Section: Hence We Have the Potentialsmentioning
confidence: 60%
“…respectively. These solutions were previously obtained by Abebe et al [23] for a radiating star which has the property of conformal flatness.…”
Section: Class IIImentioning
confidence: 78%
“…Hence we have shown that the mass flow rate is fundamentally affected by the two-fluid atmosphere with the generalised Vaidya metric since the null fluid density ρ is non-zero. Using the derivatives (22), (19) and (18) in the definitions (16) and (17) we generate the following expressions for the surface luminosity L and the asymptotic luminosity L ∞ , respectively:…”
Section: Luminosity and Gravitational Redshiftmentioning
confidence: 99%
“…Misthry et al [15] generated nonlinear exact models in the shear-free regime for relativistic stars with heat flow, using a group theoretic approach that involves the Lie symmetry analysis of the Santos junction condition. Following this, Abebe et al [16], employing the same technique, investigated the behaviour of radiating stars in conformally flat spacetime manifolds. Abebe et al [17,18] used Lie analysis to find radiating Euclidean stars with an equation of state.…”
Section: Introductionmentioning
confidence: 99%
“…The Santos junction conditions leads to a differential equation governing the temporal behaviour of the model. Solutions of this junction condition included ad hoc assumptions of the gravitational potentials, applying the method of Lie symmetries and 'spotting' of particular solutions [22][23][24].…”
Section: Introductionmentioning
confidence: 99%